Transvenous stimulation of the phrenic nerve for the treatment of central sleep apnoea: 12 months' experience with the remedē® System. (4th July 2016) - Jagielski, Dariusz; Ponikowski, Piotr; Augostini, Ralph; Kolodziej, Adam; Khayat, Rami; Abraham, William T.
Abstract: Aims: Patients with central sleep apnoea (CSA) often have poor quality of life and are at increased risk of morbidity and mortality. This study sought to evaluate the 12‐month clinical outcomes of patients with CSA treated with unilateral transvenous phrenic nerve stimulation in the prospective, multicentre, non‐randomizedrem edē ® System pilot study. Methods and results: Forty‐seven patients with CSA were treated with therem edē ® System (Respicardia Inc., Minnetonka, MN, USA) for a minimum of 3 months. Sleep‐disordered breathing parameters were evaluated by polysomnography (PSG) at 3, 6, and 12‐month follow‐up. Sleep symptoms and quality of life were also evaluated. Forty‐one patients completed all follow‐up PSGs and were included in the analysis. At 12 months, there was sustained improvement compared with baseline in the apnoea–hypopnoea index (49.9 ± 15.1 vs. 27.5 ± 18.3 events/h, P < 0.001) and central apnoea index (28.2 ± 15.0 vs. 6.0 ± 9.2 events/h, P < 0.001). Sustained improvement in the oxygen desaturation index (46.1 ± 19.1 vs. 26.9 ± 18.0 events/h, P < 0.001), rapid eye movement sleep (11.4 ± 6.1% vs. 17.1 ± 8.0%, P < 0.001), and sleep efficiency (69.3 ± 16.9% vs. 75.6 ± 17.1%, P = 0.024) were also observed. There were also continued favourable effects on sleepiness and quality of life. Three deaths unrelated torem edē ® System therapy and five serious adverse events occurred over 12 months of follow‐up. Conclusion: The present study demonstrates that in patients with CSA, unilateral transvenous phrenic nerve stimulation is associated with sustained improvement in key sleep parameters, sleep symptoms, and quality of life over 12 months of follow‐up.